2011
DOI: 10.1080/17457300.2010.503327
|View full text |Cite
|
Sign up to set email alerts
|

Parental beliefs about supervising children when crossing roads and cycling

Abstract: Pedestrian and cyclist injuries are significant public health issues, together accounting for 11-30% of road deaths in highly motorised countries. Children are particularly at risk. In Australia in 2009 11.4% of pedestrian deaths and 6.4% of cyclist deaths comprised children aged 0-16 years. Parental attitudes and level of supervision are important to children's road safety. Results from a telephone survey with parents of children 5-9 years (N = 147) are reported. Questions addressed beliefs about preventabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Cycling research has blossomed recently with many new studies (see, for example, Albert 1999; Rasanen and Summala 2000;Colwell and Culverwell 2002;Spinney 2006;Krizek, El-Geneidy, and Thompson 2007;Oddy 2007;Skinner and Rosen 2007;Spinney 2007;Horton, Rosen, and Cox 2007a;Lorenc et al 2008;Pucher and Buehler 2008;Spinney, 2008Spinney, , 2009Aldred 2010;Bonham and Koth 2010;Brown and Spinney 2010;Hopsicker 2010;Ilundáin-Agurruza and Austin 2010;Spinney 2010;Furness 2010a;McCarthy 2011;Soole, Lennon, and Haworth 2011;Spinney 2011;Aldred and Jungnickel 2012). Nevertheless, until recently, the automobile has been the primary mode of transport in many studies that are primarily concerned with social interaction and members' methods of sense-making while mobile (Watson 1999;Laurier 2002;Laurier and Philo 2002;Laurier, Lorimer, and Brown 2007;Laurier et al 2008;Noy 2009;Haddington 2010;Laurier 2010;Haddington, Keisanen, and Nevile 2012;Noy 2012).…”
Section: Interactional Mobility Studies and Mobile Video Ethnographymentioning
confidence: 98%
“…Cycling research has blossomed recently with many new studies (see, for example, Albert 1999; Rasanen and Summala 2000;Colwell and Culverwell 2002;Spinney 2006;Krizek, El-Geneidy, and Thompson 2007;Oddy 2007;Skinner and Rosen 2007;Spinney 2007;Horton, Rosen, and Cox 2007a;Lorenc et al 2008;Pucher and Buehler 2008;Spinney, 2008Spinney, , 2009Aldred 2010;Bonham and Koth 2010;Brown and Spinney 2010;Hopsicker 2010;Ilundáin-Agurruza and Austin 2010;Spinney 2010;Furness 2010a;McCarthy 2011;Soole, Lennon, and Haworth 2011;Spinney 2011;Aldred and Jungnickel 2012). Nevertheless, until recently, the automobile has been the primary mode of transport in many studies that are primarily concerned with social interaction and members' methods of sense-making while mobile (Watson 1999;Laurier 2002;Laurier and Philo 2002;Laurier, Lorimer, and Brown 2007;Laurier et al 2008;Noy 2009;Haddington 2010;Laurier 2010;Haddington, Keisanen, and Nevile 2012;Noy 2012).…”
Section: Interactional Mobility Studies and Mobile Video Ethnographymentioning
confidence: 98%
“…This research is the second stage of a study of child pedestrian fatalities, where the first stage was an in-depth analysis of the causes of child pedestrian fatal crashes. The in-depth study confirmed the importance of supervision of young children in keeping them safe around roads and vehicles as suggested by other research on child pedestrian safety (eg., Soole et al 2011;MUARC, 2010). The objective of this part of the research was to investigate changes in awareness of parents/carers, of the risk of child pedestrian injury before and after exposure to a knowledge-based campaign on child pedestrian safety.…”
Section: Introductionmentioning
confidence: 99%